1990
DOI: 10.1177/001440299105700309
|View full text |Cite
|
Sign up to set email alerts
|

Making the Transition to Postsecondary Education and Training

Abstract: A nationally representative sample of youth with disabilities who recently exited high school was studied to determine the participation of the youth in postsecondary educational programs. The results show that youth with disabilities participate in postsecondary programs at only one-quarter the rate attained by their counterparts without disabilities and at only one-third the rate attained by economically disadvantaged youth. The relationship of postsecondary education for youth with disabilities to long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 4 publications
1
27
1
Order By: Relevance
“…and without learning disabilities, roughly onethird, hoped to attain a college degree). Even so, the literature does not describe levels of postsecondary educational involvement and attainment that correspond to the educational aspirations stated by participants in this study with learning disabilities (debettencourt et al, 1989;Fairweather & Shaver, 1991;Zigmond & Thorton, 1985).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…and without learning disabilities, roughly onethird, hoped to attain a college degree). Even so, the literature does not describe levels of postsecondary educational involvement and attainment that correspond to the educational aspirations stated by participants in this study with learning disabilities (debettencourt et al, 1989;Fairweather & Shaver, 1991;Zigmond & Thorton, 1985).…”
Section: Discussionmentioning
confidence: 79%
“…Adolescents and young adults with learning disabilities ate less likely to enroll in postsecondary education (Fairweather & Shaver, 1991) and more likely to be underemployed and concentrated in lower-prestige occupations, including service, sales, and managerial fields (deBettencourt, Zigmond, & Thorton, 1989;Fourqurean, Meisgeir, Swank, & Exceptional Children Williams, 1991;Gottfredson, Finucci, & Childs, 1984;White et al, 1983).…”
mentioning
confidence: 99%
“…As more recent data sets have become available, the profession has been able to ascertain certain outcomes, such as overall employment rate (about 60%; Blackorby & Wagner, 1996;Levine & Edgar, 1995;Wagner et al, 1991), the finding that few high school graduates with learning disabilities attend college or other forms of postsecondary education programs (Affleck, Edgar, Levine & Kortering, 1990;Fairweather & Shaver, 1991;Levine, 1993;Nourse, 1995;Vogel & Adelman, 1992;Wagner et al, 1991), and that, generally speaking, youth with learning disabilities do less well than their peers without disabilities (Affleck et al, 1990;Blackorby & Wagner, 1996;Fisher & Harnisch, 1989;Levine & Edgar, 1995;Lichtenstein, 1989;Wagner et al, 1991). Another claim that has been generally accepted by the professional community is that gender is a major factor related to outcomes, with females doing less well than males (Haring & Lovett, 1990;Hasazi, Johnson, Hasazi, Gordon, & Hull, 1989;Kranstover, Thurlow, & Bruininks, 1989;Nisbet & Lichtenstein, 1992;Scuccimarra & Speece, 1990;Wagner, 1992).…”
mentioning
confidence: 99%
“…Not many students with LD attend a postsecondary school to continue their education (Fairweather & Shaver, 1991;Valdes, Williamson, & Wagner, 1990). The ratio is approximately three to one nondisabled to students with LD who attend a postsecondary school within a year after leaving high school.…”
Section: Student Characteristics Who Transitionsmentioning
confidence: 99%
“…Students with LD will not likely be alone as they attend a postsecondary setting. Several estimates suggest that LD represents one of the largest groups of students with disabilities on campus (CLD, 1993;Fairweather & Shaver, 1991). Fairweather and Shaver found that 17% of students with LD enrolled in some type of course in a postsecondary setting-8.5% in a vocational course, 6.8% in a 2-year course, and 1.8% in a 4-year course.…”
Section: Student Characteristics Who Transitionsmentioning
confidence: 99%